2002
DOI: 10.1152/ajpheart.00382.2001
|View full text |Cite
|
Sign up to set email alerts
|

Potassium (BKCa) currents are reduced in microvascular smooth muscle cells from insulin-resistant rats

Abstract: Insulin resistance (IR) syndrome is associated with impaired vascular relaxation; however, the underlying pathophysiology is unknown. Potassium channel activation causes vascular smooth muscle hyperpolarization and relaxation. The present study determined whether a reduction in large conductance calcium- and voltage-activated potassium (BK(Ca)) channel activity contributes to impaired vascular relaxation in IR rats. BK(Ca) channels were characterized in mesenteric microvessels from IR and control rats. Macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
7
41
0
1
Order By: Relevance
“…Using immunoblot analysis we found that levels of the BK Ca ␣, Kir6.1-6.2, and Kir2.1 proteins (the pore-forming subunits of the BK Ca , K ATP , and K ir -channels, respectively) are not detectably affected by IR. These findings are consistent with the results of a previous study (46) in which the expression of the BK Ca ␣ subunit in mesenteric arteries was found to be unaffected by IR, although the same channel subunit has been found to be upregulated in other vascular disease states (33).…”
Section: Fig 4 Responses To Increases In the Extracellular K ؉ Concsupporting
confidence: 93%
“…Using immunoblot analysis we found that levels of the BK Ca ␣, Kir6.1-6.2, and Kir2.1 proteins (the pore-forming subunits of the BK Ca , K ATP , and K ir -channels, respectively) are not detectably affected by IR. These findings are consistent with the results of a previous study (46) in which the expression of the BK Ca ␣ subunit in mesenteric arteries was found to be unaffected by IR, although the same channel subunit has been found to be upregulated in other vascular disease states (33).…”
Section: Fig 4 Responses To Increases In the Extracellular K ؉ Concsupporting
confidence: 93%
“…Single-channel currentvoltage relationships yielded an average single-channel conductance of 142 Ϯ 5 pS (n ϭ 3; Fig. 2B), which agrees with other studies reporting BK Ca channel conductance in vascular smooth muscle (6,11). Furthermore, raising Ca 2ϩ concentration at the cytoplasmic face of the patch membrane increased channel gating dramatically (Figs.…”
Section: Identification Of Right Ventricular Hypertrophysupporting
confidence: 90%
“…Whole cell currents were measured from metabolically intact PASMC using the amphotericinperforated-patch technique (6,11). In contrast to standard whole cell techniques, perforated-patch recordings provide accurate current measurement with only minimal current decay or loss of soluble cytoplasmic components due to cellular dialysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All drugs were diluted into fresh bath solution (1 ml) and perfused into a 2-ml recording chamber (Warner Instruments). Channel activity was quantified by calculating the single channel open probability (NP o) over the duration of the entire data file, as described previously (10,12,39,40).…”
Section: Animalsmentioning
confidence: 99%